Abstract “why” Thoughts About Success Lead to Greater Positive Generalization in Sport Participants - Van Lier, Jens; Moulds, Michelle L.; Raes, Filip (Frontiers in Psychology, 2015)
Generalizing from a single failure or success to future performances and their self-concept could have an important impact on sport participants. This study examined the impact of the way sport participants think about success on positive generalization. Sport participants (N=222) completed an online experimental study in which they were induced to think about meanings, causes and implications (i.e., abstract-‘why’-thinking) or about more perceptual concrete aspects of their performance (i.e., concrete-‘how’-thinking). We hypothesized that abstract-‘why’-thinking would lead to greater positive generalization and that this effect would be moderated by self-esteem. Our results supported our hypothesis that abstract thinking increased positive generalization, and this effect was more clearly visible in sport participants with higher self-esteem. These results suggest that retrospective thinking about the ‘why’ of a good performance may benefit athletes in the long run because they generalize the outcome to future performances and their self-concept which may boost their motivation and consequently their performance.